Is neoadjuvant chemotherapy necessary for patients with initially resectable colorectal liver metastases in the era of effective chemotherapy? - Son, Sang-Yong (Korean J Hepatobiliary Pancreat Surg, 2011)
BACKGROUNDS/AIMS: Hepatic resection has only guaranteed long-term survival in patients with colorectal liver metastasis (CRLM) even in the era of effective chemotherapy. The definite role of neoadjuvant chemotherapy (NCT) is to improve outcomes of unresectable CRLMs, but it its role has not been defined for initially resectable CRLMs (IR-CRLMs). METHODS: We reviewed the medical records of 226 patients, who had been diagnosed and treated for IR-CRLM between 2003 and 2008; the patients had the following pathologies: 10% had more than 4 nodules, 11% had tumors larger than 5 cm, and 61% had synchronous CRMLs. Among these patients, 20 patients (Group Y) were treated with NCT, and 206 (Group N) did not receive NCT according to their physician's preference. The median follow-up time was 34.1 months. RESULTS: The initial surgical plans were changed after NCT to further resection in 20% and to limited resection in 10% of 20 patients. Complication rates of Groups Y (30%) were indifferent from Group N (23%) (p=0.233), but intraoperative transfusions were more frequent in Group N (15%) than in Group Y (5%) (p=0.006). There was one case of hospital mortality (0.44%). Disease-free survival rates in Groups Y and N were 23% and 39%, respectively, and patient survival rates were 42% and 66% (p>0.05). By multivariate analysis, old age (≥60 years), differentiation of primary tumor (poorly/mucinous), resection margin involvement, and no adjuvant chemotherapy were associated with poor patient survival; the number of CRLMs (≥4) was associated with poor disease-free survival. CONCLUSIONS: NCT had neither a positive impact nor a negative impact on survival, even with intraoperative transfusion, as observed on operative outcomes for patients with IR-CRLM. Further study is required to elucidate the role of NCT for treatment of patient with IR-CRLMs.